Islamic work ethics and accounting practices in Indonesia: a study on fraud - Wuryaningsih, Wuryaningsih; Wafiroh, Novi Lailiyul (LPPM ISNJ Bengkalis, 2025)
Purpose – This research aims to examine the effect of attitudes and subjective norms on intentions to commit fraud in financial reports. Furthermore, this research also investigates the effect of Islamic work ethics (IWE) on fraudulent intentions in financial reports. Method – A quantitative research design was implemented, with primary data obtained from an online survey. The target population included accounting practitioners and future accountants in Indonesia. Purposive sampling was employed, resulting in a sample of 147 respondents. Data analysis was performed using SEM-PLS, specifically with SMART-PLS 4.0 software. Findings – The results of this research show that attitudes and subjective norms positively and significantly affect fraud intentions in financial reports. In contrast, Islamic work ethics do not affect fraudulent intentions in financial reports. Implications – Theoretically, this research implies that the theory of reasoned action (TRA) can strongly predict fraud within financial statements. However, this study could not demonstrate that the Islamic work ethic directly influences fraudulent intentions. This does not necessarily imply that IWE is irrelevant. This suggests a more indirect or intricate influence, potentially through shaping moral values that affect attitudes and subjective norms in the theory of reasoned action. In practice, this study can guide educational institutions and accounting organizations in developing anti-fraud education programs within academic settings and through professional development.